Analysis and reliability of separable systems. (2021) - Cancela, Héctor; Guerberoff, Gustavo; Robledo, Franco; Romero, Pablo
Abstract: The operation of a system, such as a vehicle, communication network or automatic process, heavily depends on the correct operation of its components. A Stochastic Binary System (SBS) mathematically models the behavior of on-off systems, where the components are subject to probabilistic failures. Our goal is to understand the reliability of the global system. The reliability evaluation of an SBS belongs to the class of NP-Hard problems, and the combinatorics of SBS imposes several challenges. In a previous work by the same authors, a special sub-class of SBSs called separable systems was introduced. These systems accept an efficient representation by a linear inequality on the binary states of the components. However, the reliability evaluation of separable systems is still hard. A theoretical contribution in the understanding of separable systems is given. We fully characterize separable systems under the all-terminal reliability model, finding that they admit efficient reliability evaluation in this relevant context. Highlights: We introduce the definition of Separability in the context of Stochastic Binary Systems. We study the complexity of Separable Systems. We state characterizations for Separable Systems. We study the particular case of reliability for the all-terminal model for graphs. We introduce generalizations for the concept of planar separability.